Photosynthetic Microorganisms Mechanism For Carbon Concentration - Singh, Shailendra Kumar; Sundaram, Shanthy; Kishor, Kaushal; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book provides a cohesive overview of carbon concentrating mechanism (CCM) of photosynthetic microorganisms such as cyanobacteria and microalgae. This unique mechanism is by far the most spectacular physiological process in algal growth and productivity. Due to this fact, the study of CCM has captivated phycologists, algal molecular and cellular biologists, botanists, agriculturalists, crop growers, and most recently algal biofuel researchers, around the world. In the brief, the authors draw a contextual in-depth overview, on the basis of the latest findings, to develop an account of the core concepts regarding state-of-the-art of CCM. Subsequent chapters use this account to explore carbon concentrating mechanism of cyanobacteria and microalgae. They highlight the concise summaries of cutting-edge research and integrated industrial applications of photosynthetic microorganism based CO2 mitigation system, across a wide spectrum of energy and environment. The brief also presents sustainable perspectives of carbon concentrating mechanism in the context of current global energy and environmental challenges.
Introduction -- Carbon concentrating mechanism -- Carbon concentrating mechanism of cyanobacteria -- Carbon concentrating mechanism of microalgae -- Photosynthetic microorganisms based mitigation system: Integrated approaches for global sustainability.
Keywords: Materials science; Renewable energy resources; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Renewable energy sources; Alternate energy sources; Green energy industries; Biomaterials; Materials Science; Biomaterials; Renewable and Green Energy; Engineering Thermodynamics, Heat and Mass Transfer; Electronic books